Disruption to schooling: Evidence from volcano eruptions on Java Island, Indonesia - Elghafiky Bimardhika; Lolita Moorena (Asian Development Bank Institute (ADBI), 2024)
Volcanic eruption is a frequent occurrence in Indonesia, especially on the densely populated Java Island; therefore, policy to improve resilience in children's education is an important avenue. We examine the causal impact of the 2010 Mt. Merapi and 2014 Mt. Kelud eruptions on children's school continuation. We utilize triple difference with continuous treatment estimation and find that a volcanic eruption reduces the likelihood of children being enrolled in school and that the effect can worsen over time. The effect is likely driven by the reallocation of education spending to essential household durables spending to cope with the aftermath of the disaster. Heterogeneity analysis reveals that the impact is more pronounced for girls, oldest children, primary-school-aged children, and children living in poor households. Children experience earlier transitions to the labor force as a consequence of the disruption. To formulate policy recommendations, we conduct a mediation analysis and find that school infrastructure, the pupil-teacher ratio, and telecommunication networks are important factors mediating the volcano eruption's negative impact.
Keywords: I21; Q54; J13; 330; volcano eruption; school enrollment; education resilience